LABOR MARKET OF VOLYN REGION: STATISTICAL RESEARCH ON ECONOMIC ACTIVITY OF POPULATION (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. Changes in the economy of Ukraine require solving the problem of forming a competitive labor market. This requires the definition of priority areas for regulation of the labor market and employment at the national and regional levels, which require adequate statistical and information-analytical support.The purpose of the article is to conduct a multidimensional statistical analysis of the labor market of Volyn region for the period 2013-2018.Results. A multidimensional statistical survey of the labor market is needed to make sound management decisions at the micro, meso and macro levels. It involves assessing the market situation for employment and unemployment, characterizing trends and market proportions, determining efficient demand and supply. The article presents the results of the first stage of a comprehensive statistical analysis of the Volyn region's labor market in 2013-2018, namely economic activity of the population by age categories, employed and unemployed population. Comprehensive statistical analysis showed that economic activity indicators were the best in 2016, they had worsened in 2017 and increased slightly in 2018 but did not reach levels in 2016. The level of economic activity of the region's population decreased by 13,7% over five years, the employment rate decreased by 17,1%, the unemployment rate increased by 46,2%.A comparative analysis of trends in the number of economically active and economically inactive population of Volyn region with the same in Ukraine shows that the trends are the same, but the indicators characterizing the region's labor market in 2013-2018 are worse than in Ukraine.Structural changes in the number of economically active population by type of education are insignificant.Conclusions. The level of economic activity of the population of the region in the five years has significant decreased by 13,7%, the employment rate decreased by 17,1%, the unemployment rate increased by 46,2%, which is a negative trend.
Keywords: labor market, economically active population, employed population, unemployed population